2012
DOI: 10.1111/j.1748-5991.2011.01123.x
|View full text |Cite
|
Sign up to set email alerts
|

The many uses of regulatory impact assessment: A meta‐analysis of EU and UK cases

Abstract: Research on regulation has crossed paths with the literature on policy instruments, showing that regulatory policy instruments contain cognitive and normative beliefs about policy. Thus, their usage stacks the deck in favor of one type of actor or one type of regulatory solution. In this article, we challenge the assumption that there is a predetermined relationship between ideas, regulatory policy instruments, and outcomes. We argue that different combinations of conditions lead to different outcomes, dependi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
83
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 75 publications
(87 citation statements)
references
References 40 publications
1
83
0
2
Order By: Relevance
“…The literature on IA (Radaelli 2010;Dunlop et al 2012) provides support for this argument by reference to a range of aspects which highlight the potential role of IA as an accountability instrument. Firstly, prior studies of IA indicate that, in the context of delegated policy making, the instrument can promote greater and more dynamic forms of political control over the regulator's decisions by the political principal, such as government, an upper-level executive or affiliated regulatory authority.…”
Section: Regulatory Accountability and Iamentioning
confidence: 98%
See 4 more Smart Citations
“…The literature on IA (Radaelli 2010;Dunlop et al 2012) provides support for this argument by reference to a range of aspects which highlight the potential role of IA as an accountability instrument. Firstly, prior studies of IA indicate that, in the context of delegated policy making, the instrument can promote greater and more dynamic forms of political control over the regulator's decisions by the political principal, such as government, an upper-level executive or affiliated regulatory authority.…”
Section: Regulatory Accountability and Iamentioning
confidence: 98%
“…Finally, organizations such as IRAs may use knowledge symbolically to gain legitimacy in the eyes of significant stakeholders or other policy actors and also to conform to the logic of appropriateness that encourages them to make an appropriate response to external pressures and expectations (Schrefler 2010). While, as we discussed earlier, IA can be used to project the image of rational policy making (Radaelli 2010), prior studies have also demonstrated that the ideas behind IA and the actual application of those are often decoupled, pointing to the widespread occurrence of what Dunlop et al (2012) termed the 'perfunctory' use of the instrument. In this vein, Schrefler (2010) further argues that the reliance on knowledge instruments (such as IA) can have a protective function in certain policy sectors (for example, regulation of professional services) where there is strong isomorphic pressure on regulators to be seen to make reference to expertise and research findings.…”
Section: The Role Of Ia In the Context Of Irasmentioning
confidence: 99%
See 3 more Smart Citations